Sweet sorghum (Sorghum dochna L.) restorer lines effects on nutritional parameters of stalk juice - Erdei, Éva; Pepó, Pál; Csapó, János; Tóth, Szilárd; Szabó, Béla (Acta Agraria Debreceniensis, 2009)
Sweet sorghum can be utilized for bioethanol production because it has high sugar content (14-17%). We determined the most important nutritional values of 5 silo type sorghum lines in waxy and full maturation. The examined restorer lines were: RL 4, RL 9, RL 15, RL 18, K 1. The following nutritional parameters were examined: dry material content, refractometric total sugar content, reducing sugar content. In waxy maturation 73.85-87.37% of dry matter in stalk juice makes the total sugar. Dry  material content, total and reducing sugar content of stalkdecreases from waxy mature to full maturation.There are differences between lines in dry matter (SzD5%=0.76), total sugar (SzD5%=0.79), reducing sugar content (SzD5%=0.30). RL 4 performed a decrease in total sugar content from 10.07% to 10.02% during this period, reducing sugar also decreased from 4.01% to 2.47%. RL 9 performed a decrease in total sugar content from 11.76% to 11.08% during this period. Reducing sugar also decreased from 3.17% to 2.01% in the waxymaturation. RL 15 showed a total sugar content decrease from 15.43 % to 15.36%. The reducing sugar also decreased from  3.23% to 1.71% in waxy maturation. In RL 18 total mean sugar content during waxy maturation was 13.78% which dropped to 13.26% approaching full maturation. Reducing sugar also decreased from 4.11% to 2.23% in waxy mature. K 1 performed a decrease in total sugar content from 9.35% to 6.15% during this period, while reducing sugar also decreased from 1.52% to 0.77%. These lines upcoming for experiments are perspectives since having excellent stalk juice nutritional parameters they are of great or very great height and their stalks are thick-very thick, stalk medullas are wet.